3-4 JASAR BALALARDI OYIN - SHINIǴIWLARǴA HÁM SHET TILLERDE SANAWǴA ÚYRETIW - Qochanov, Sh.J. (SCIENCE and SOCIETY, 2022)
The article deals with teaching children 3-4 years of age physical exercises and counting in Karakalpak, Uzbek, Russian and English.